A Content Analysis Study towards Researches Regarding Context-Based Learning Approach in Science Education by Between Years 2010 and 2020 in Turkey - Büşra Arik Güngör; Mustafa Metin; Sibel Saraçoğlu (Journal of Science Learning, 2022)
The purpose of this study is to study research regarding the context-based learning approach in science education between 2010 and 2020 in Turkey. In this study, a descriptive content analysis method was used to analyzed 86 articles on context-based learning in science education published in 67 different journals. According to some variables such as the year of publication, purpose, area, method, sample, number of samples, data collection tool and data analysis techniques. The Research Classification Form developed by the researchers was used in the analysis of the data. The data were analyzed using descriptive content analysis. Most studies in the field of context-based learning approaches in science education were published in 2019. Most of the studies aimed to determine the effects of the method on achievement and attitude and were carried out within science. The experimental method was preferred among the quantitative methods in the studies. Most of the studies were conducted with secondary school students, and the number of participants was in the range of 0-100. Achievement tests and attitude scales were used extensively as data collection tools, and content analysis and t-test were used extensively in data analysis techniques. According to the results obtained in the research, it is suggested that the researches on the context-based learning approach should be conducted in areas other than science education.